Perlindungan Diskriminasi terhadap Disabilitas dalam Lingkup Pendidikan - Putri, Filzah Arina (Universitas Batanghari Jambi, 2024)
Protection against disability discrimination in education is essential to ensure that all individuals, without exception, have a fair chance to learn and develop. Inclusive regulations and policies as well as data related to the challenges faced by people with disabilities can be the basis for improving the quality of inclusive education in Indonesia and the world. Based on this problem, further discussion is needed regarding how the government's efforts to provide legal protection to overcome acts of discrimination against people with disabilities and how the government can provide fair treatment for people with disabilities to obtain the right to a decent education. The approach methods used are the Statute Approach, the Historical Approach, and the Conceptual Approach. The results of the study show that the government actually still pays less attention to matters related to protection against discrimination against people with disabilities in the scope of education.